EKSISTENSI HUKUM TERHADAP KEAMANAN RAHASIA BANK DALAM MENJAGA KEPENTINGAN NASABAH DITINJAU DARI UNDANG-UNDANG PERLINDUNGAN KONSUMEN NO 8 TAHUN 199 - Hotman Sinambela (PT Sanagi Edu Konsultan, 2025)
The increasing sophisticated crime mode, in this case Bank Indonesia in efforts to overcome criminal acts in banking is very necessary and banking can find solutions through efforts that can be done to overcome crimes in banking. The problem is How Effective is the Consumer Protection Law no. 8 of 1998 in providing legal protection for banking in Indonesia? What obstacles arise against the Existence of Law Number 10 of 1998 Concerning Banking? The research method used is a literature study (library research) normative legal approach, namely setting certain normative standards for a phenomenon by reviewing secondary data and discussing the Existence of Law no. 10 of 1998 Concerning Banking in overcoming Banking Crimes. Based on the discussion above, the author concludes that the existence of Law Number 10 of 1998 concerning Banking is not yet effective, this is because there are still many consumer protection, law enforcement officers who have not been able to provide certainty, justice, and legal benefits proportionally, certainty and speed of case resolution depend on the supporting facilities available.